(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2022)
A wireless sensor network is a group of specialized transducers with a communications infrastructure for monitoring and recording conditions at diverse locations. Commonly monitored parameters are humidity, pressure, temperature, wind direction and speed, vibration intensity, illumination intensity, sound intensity, chemical concentrations, power-line voltage, pollutant levels and vital body functions. A wireless network communication become a common for any data and IEEE 802.11 is a used for wireless LAN communication because of its simplicity system. Wireless sensor node deployment deferent topology are frequently changed are for the using sensor node. In this paper analysis and improve energy consumption for using different node 50, 100 and 150 using K-mean, fuzzy and SOM algorithm with five cluster and as a result to increase the network life time, using fuzzy logic inference system using Matlab R2013a Simulation tools.